Lipid profile changes after the acute COVID-19 period. Sub-analysis of the International Registry "Dynamics Analysis of Comorbidities in SARS-CoV-2 Survivors" (AKTIV SARS-CoV-2)" (12-month follow-up) - G. P. Arutyunov; E. I. Tarlovskaya; A. G. Arutyunov; D. S. Polyakov; N. Yu. Grigorieva; I. V. Gubareva; U. K. Kamilova; Z. F. Kim; A. S. Kuznetsova; T. Yu. Kuznetsova; D. Yu. Ruzanov; A. V. Svarovskaya; et al. (Российский кардиологический журнал)
Aim. To analyze the lipid profile changes during the acute phase of coronavirus disease 2019 (COVID-19) and within 12 months after discharge from the hospital (post-Covid period) in comparison with the lipid profile of patients before COVID-19.Material and methods. The subanalysis of the registry was carried out as follows: clinical investigators in each of the centers included patients in the AKTIV registry selected from the database patients who met three following criteria: (1) availability of lipid profile test no more than 60 days before COVID-19; (2) availability of lipid profile test during the acute period; (3) availability of lipid profile test within 6-12 months after discharge from the hospital.Results. In patients after COVID-19, a decrease in the levels of all lipid profile parameters in the acute COVID-19 phase and their subsequent increase were found.In the post-COVID-19 period, 25,7% of patients experienced an increase in lipid profile parameters (increased levels of total cholesterol (TC) and/or cholesterol, low-density lipoproteins and/or triglycerides and/or cholesterol excluding high-density lipoproteins by ≥0,5 mmol/l) despite the fact that lipid-lowering therapy in these patients was at least no worse than in patients without lipid profile changes.Multivariate analysis found that such variables as age (direct relationship), body mass index (direct relationship), estimated glomerular filtration rate in the acute phase (inverse relationship) and cholesterol level excluding high-density lipoproteins in the acute period (inverse relationship), as well as heart failure, obesity and cytokine storm in the acute COVID-19 phase are independent predictors of an increase in one or more lipid parameters by ≥0,5 mmol/l over 6-12 months of post-COVID-19 period.Conclusion. COVID-19 likely contributes to the onset and/or progression of lipid metabolism disorders in COVID-19 survivors (Eurasian population).